Results of acceptance tests of the machine for extraction and scarification of clover seeds КС-0.2 - A. I. Burkov; M. V. Simonov; V. Yu. Mokiev (Аграрная наука Евро-Северо-Востока, 2016)
Prototype of the machine for extraction and scarification of clover seeds КС-0.2 was tested. The machine is used for extraction of seeds from the wad of clover and scarification of hard grass seed. The purpose of the test -determination of agro-technical, operational-technological, economic performance of machines; safety indicators, ergonomics and reliability of the machine. Verification of its conformity to requirements of the technical specifications (TS) and normative documentation (ND). Wad of clover Kirovskij-159 was used for extraction of seeds. Seeds of Galega orientalis were used for scarification of seeds according to requirements of State standard 52323-2005. The test results revealed that the machine is functioning and efficiently performs processes of extraction of seeds from the wad of clover and scarification of hard grass seed. The machine complies with the basic requirements by assignment, reliability, security, and parameters of operation and technologies. The machine provides degree of seeds extraction 97.5.94.4 %, crushing of seeds 0.82.0.31% with productivity 0.16.0.38 t/h; degree of scarification of seeds 98.7.99.1%, crushing of seeds 1.2...1.6 % with productivity 0.19.0.33 t/h. Machine fits into the technology of seed production of perennial grasses and is recommended for use in agricultural production.